Kolaborasi Pemerintah Daerah dalam Pelestarian Tradisi Lisan Iko-Iko Suku Bajau di Sulawesi Tenggara - Abdul Hakim (Jurnal Pemerintahan dan Politik Lokal, 2022)
The purpose of this study is to examine the collaboration between the government and the private sector (PT. Antam. Tbk) and the collaboration between the government and the community/NGOs (MediaQita Foundation) in preserving the oral tradition of the Bajau Iko-Iko in Southeast Sulawesi. The research method in this article is a qualitative with a descriptive approach. The data sources of this research are primary and secondary with data collection techniques through interviews, observation and documentation. The results of this research are the collaboration between the government and the private sector (PT. Antam. Tbk) and the collaboration between the government and the community/NGOs (MediaQita Foundation) in preserving the oral tradition of the Bajau iko-iko in Southeast Sulawesi. The presence of a culture-based curriculum in three elementary schools in the coastal area of ​​Hakatotubu Village.